Furniture Skills Training for Prisoner in Class IIA Prison - Sofyan Syahputra (Universitas Negeri Padang, 2021)
This research is motivated by how the Furniture Skills Training Activities organized by the Karawang Class IIA prison take place. This furniture skills training activity is a part of the coaching program at the institute. With the aim that the fostered citizens are more skilled and more formed daily character both in the prison environment and when later after being free of sentence. This research approach used is qualitative research with descriptive research type. With the subject of research 1 prison officer, 1 instructor and 2 prisoners who participated in furniture skills training activities. The instrument used is Observation, Interview and documentation so that the expected data can be obtained optimally. The results obtained in this study are: 1) knowing the process of furniture skills training held by class IIA prison in Karawang . 2) find out the inhibiting factors for furniture skills training for prisoners in class IIA prison in Karawang. 3) find out the results achieved for prisoners in class IIA prison in KarawangKeywords: fostering skills in prisons, furniture training in prisons